ROCK FORMATION AND SITE CLASS IN BANDAR LAMPUNG - Rustadi Rustadi; Eko Rananda (Engineering Faculty Universitas Lampung, 2020)
Soil characteristics are important impact for the scale of damage caused by earthquake vibrations. The impact caused by an earthquake in a location depends on the shear wave velocity (Vs). The study examined the effect of sedimentary rock formations on shear wave velocity and site class based on SPT tests in two rock formations in Bandar Lampung. The value of Vs, Vs30 and site class is determined based on the N-SPT value. Older rock formations of Quaternary age, have produced compaction at a shallow depth of 2 m from the surface, with Vs30 360 m/s and site class C. While the formation is younger, compactions are formed at a depth of 20 m, Vs 30 200 m/s and site class D.